2022
DOI: 10.7759/cureus.24794
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus and Hepatitis C Virus in Patients Undergoing Maintenance Hemodialysis

Abstract: Background Underdeveloped countries suffer a huge burden of infectious diseases, among which hepatitis B virus (HBV) and hepatitis C virus (HCV) are of major concern. Our study sought to determine the seroconversion rate for HBV via hepatitis B antigen (HBsAg) and HCV via anti-hepatitis C virus antibodies (anti-HCV) among patients on maintenance hemodialysis in the dialysis unit of a tertiary care hospital in Pakistan. Methodology This study was carried out from October 2020 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…14 20% of patients with CKD had hepatitis C antibodies, according to research by Fabrizi et al Hepatitis C antibodies were found in 3.9% and 7.0% of participants in dierent investigations. 15,16,17,18 Variations in hepatitis C prevalence among geographical regions, study periods, methods for detecting hepatitis C antibodies, and infection control practices between nations are likely to be the causes of inconsistent results. Despite Pakistan's high hepatitis C prevalence, CKD patients in our study had a much greater frequency of hepatitis C antibodies than the overall population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 20% of patients with CKD had hepatitis C antibodies, according to research by Fabrizi et al Hepatitis C antibodies were found in 3.9% and 7.0% of participants in dierent investigations. 15,16,17,18 Variations in hepatitis C prevalence among geographical regions, study periods, methods for detecting hepatitis C antibodies, and infection control practices between nations are likely to be the causes of inconsistent results. Despite Pakistan's high hepatitis C prevalence, CKD patients in our study had a much greater frequency of hepatitis C antibodies than the overall population.…”
Section: Discussionmentioning
confidence: 99%
“…Other research in the CKD population has linked hepatitis C to low creatinine clearance, transfusion history, longer duration of CKD, history of intravenous drug use, and increased ALT values. 14,17,18 The ndings of our investigation have various ramications. First, to stop the spread of infection to other patients and medical personnel, stringent universal infection control measures should be implemented in hospital wards where CKD patients are admitted.…”
Section: Discussionmentioning
confidence: 99%
“…While a similar link was not seen in the patients who had seropositivity for hepatitis B surface antigen, the correlation between the duration of haemodialysis and viral indicators was significant (p=0.05) for the patients who had been screened positive for anti-HCV. 11 Results of an Indian study in 2022 showed that 11.66% of patients tested positive for hepatitis B surface antigen, while 31.68% of patients had anti-HCV antibodies found. While the majority of HCVpositive patients were between the ages of 41 and 50 (23.07%), the majority of anti-HBV-positive patients were in the >60 age group (11.53%).…”
Section: Evidence From Literaturementioning
confidence: 99%
“…Hepatitis C virus (HCV) is a common cause of chronic liver disease which is a progressive worldwide health problem of a major concern in underdeveloped countries (Ahmed et al, 2022). HCV is a significant pathogen for induction of hepatic fibrosis, cirrhosis as well as liver failure and hepatocellular carcinoma (HCC), which is the most common primary liver cancer (Ben Shabbir et al, 2022). The pathogenesis of HCV chronic liver disease is still a matter of debate, one of the possible mechanisms is the induction of dysregulation of the innate and adaptive immune responses through affecting the functions of the monocytes, which play a crucial role in linking innate and adaptive immunity to control viral infection (Pang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%